2018
DOI: 10.1001/jamapediatrics.2017.5763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical and Medical Therapy for Type 2 Diabetes in Severely Obese Adolescents

Abstract: ; for the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) and Treatment Options of Type 2 Diabetes in Adolescents and Youth (TODAY) Consortia IMPORTANCE Because of the substantial increase in the occurrence of type 2 diabetes in the pediatric population and the medical complications of this condition, therapies are urgently needed that will achieve better glycemic control than standard medical management. OBJECTIVE To compare glycemic control in cohorts of severely obese adolescents with type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(92 citation statements)
references
References 32 publications
3
87
0
2
Order By: Relevance
“…In addition, we found a decrease in the in-hospital postoperative complication rates to 2.0%. A recently published study conducting a secondary analysis of data previously collected by the Teen Longitudinal Assessment of Bariatric Surgery and Treatment Options of Type 2 Diabetes in Adolescents and Youth trials 4 found adolescents with severe obesity treated with MBS had better weight loss, glycemic control, and improvement of cardiovascular risk markers than those receiving medical treatment alone. Despite these findings, less than 0.04% of children and adolescents with severe obesity are treated with MBS each year.…”
Section: Discussion ∣mentioning
confidence: 99%
“…In addition, we found a decrease in the in-hospital postoperative complication rates to 2.0%. A recently published study conducting a secondary analysis of data previously collected by the Teen Longitudinal Assessment of Bariatric Surgery and Treatment Options of Type 2 Diabetes in Adolescents and Youth trials 4 found adolescents with severe obesity treated with MBS had better weight loss, glycemic control, and improvement of cardiovascular risk markers than those receiving medical treatment alone. Despite these findings, less than 0.04% of children and adolescents with severe obesity are treated with MBS each year.…”
Section: Discussion ∣mentioning
confidence: 99%
“…Furthermore, adolescence is a unique developmental period characterized by complex physiological and psychosocial changes and challenges that may complicate obesity management . Growing evidence supports the efficacy and safety of paediatric bariatric surgery . However, a better understanding of factors associated with successful surgical outcomes is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In a parallel analysis in youth-onset T2D who underwent bariatric surgery (Teen-LABS) vs. medical management (TODAY), the proportion of participants in Teen-LABS with elevated albumin excretion decreased from 26% to 5% over 2 yrs. Conversely, the prevalence of elevated albumin excretion did not change over time in TODAY (43). No data exist on the effect of bariatric surgery on hyperfiltration, intrarenal hemodynamic function, or renal O 2 in youth-onset T2D (Figure 4).…”
Section: Potential Novel Therapies For Hyperfiltrationmentioning
confidence: 88%